Impact of the covid-19 epidemic on the relationship between R&D and firm performance - a comparative analysis of state-owned and non-state-owned enterprises in the Chinese pharmaceutical manufacturing industry and information technology industry - XIANG, HE (2022)
The COVID-19 epidemic has had a significant impact on global firms. The purpose of this paper is to examine the impact of the COVID-19 epidemic on the relationship between R&D investment and firm performance in Chinese pharmaceutical manufacturing and information technology industries. Our sample includes all data for the five-year period 2017-2021 for Chinese listed companies in the pharmaceutical manufacturing and information technology industry. The empirical results show that， under the influence of covid-19, the negative impact of R&D Expenditure on firm performance is stronger for SOEs listed in Chinese pharmaceutical manufacturing and information technology industries than for non-SOEs, but the negative impact of R&D intensity on firm performance is lower for SOEs than for non-SOEs. This finding may have implications for business managers and policymakers in planning corporate R&D more rationally in the covid-19 period.